Sleep disorders, stress coping strategies and neurobehavioral aspects: an outlook on the impact of covid‑19 in first‑year resident physicians - Teodoro, Michele; Italia, Sebastiano; Giambò, Federica; Costa, Chiara; Fenga, Concettina (Biomedical reports, 2024)
The COVID-19 pandemic had a profound impact on the physical and mental health of healthcare professionals. The present study explored the relationship between sleep disorders, stress, coping strategies and neurobehavioral aspects among young physicians during the second wave of the COVID-19 pandemic. Through a multi-assessment approach, this cross-sectional study collected sociodemographic and occupational data from first-year resident doctors in southern Italy. Subjective sleep quality, chronotype, work-related stress, coping approach and mood state were assessed by administering validated questionnaires during face-to-face interviews. Among the 258 resident physicians enrolled in the study, ~25% complained of poor sleep quality, mainly male subjects [odds ratio (OR), 2.52]. Alcohol consumption resulted as a risk factor for poor sleep quality (OR, 1.97). None of the participants reported work-related stress showing, on the contrary, a high score for the vigor factor in the profile of mood state, in particular in subjects with previous working experience with COVID patients and prevention (P<0.040 and P<0.035, respectively). Women were more likely to adopt coping strategies that involved the search for social support, confirming their tendency to manage stressful situations through emotion-focused mechanisms. The set of these results represents a sight on the attitude of young physicians in their approach to facing the COVID-19 pandemic, in its second wave. The pandemic has turned the spotlight on the importance of prevention and early diagnosis of physical health and mental well-being. Further studies are performed to monitor long-term consequences on health status.